Changes in the isoflavone profile and in the chemical composition of tempeh during processing and refrigeration - Ferreira, Márcia Pires; de Oliveira, Maria Cristina Neves; Mandarino, José Marcos Gontijo; da Silva, Josemeyre Bonifácio; Ida, Elza Iouko; Carrão-Panizzi, Mercedes Concórdia (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to analyze changes in the isoflavone profile, determined by high performance liquid chromatography, at different processing stages and after refrigeration of tempeh. For tempeh production, clean soybean grains from cultivars BR 36 (low isoflavone content) and IAS 5 (high) were dehulled, and the separated cotyledons were hydrated and then cooked in boiling water for 30 min. Spores of the Rhizopus microsporus var. oligosporus fungus were inoculated in the cooked and cooled cotyledons, and incubated at 32ºC for 6, 12, 18, and 24 hours in perforated polypropylene bags, for fermentation. The resulting tempeh was stored at 4ºC for 6, 12, 18, and 24 hours. After 24-hour fermentation, isoflavone glucosides were 50% reduced, and the aglycone forms in the tempeh from both cultivars was increased. The malonyl forms reduced 83% after cooking. Less than 24 hours of refrigeration did not affect the isoflavone profile of tempeh from either cultivar, which is a good indicator of its quality. The tempeh maintains the high and low isoflavone content of the cultivars, which indicates that cultivar differences in this trait should be considered when processing tempeh.